The relationship between leadership factors and successful technopreneur through the mediator role of digital enabler - Al-Shami, Samer Ali Hussein; Alkhoori, Ahmed Abdulqader; Sidek, Safiah (Webology Center, 2021)
The business digitalization wave has changed the entrepreneurship landscape globally. The existing digital enabler practices and thinks differently through making an item or arrangement that utilizes the ability of innovation to change the way was customarily done, especially in UAE. The power of technology completely changed the economics of an industry, where entrepreneurial venture aims to meet a marketplace or a platform that require them to transform into digital enablers as a successful technopreneur. This research aims to develop a new leadership model for successful technopreneur in the UAE. Adapting the theory of planned behaviors to predict a person's goal to participate in technology behavior and the transformational leadership theory that focuses on a leader towards identifying technology needs for better performance. A survey approach as a primary data collection was applied to test concepts and reflect the attitude of 323 respondents among technopreneur from the Innovation and Entrepreneur Centre located in Abu Dhabi. The data were analyzed through SmartPLS software for Structural Equation Modelling (SEM) using the Partial Least Squares (PLS) path modeling method that indicates that leadership factors of authenticity, devolved decision making, agility, collaborative achievement, and purpose and direction have a positive relationship towards successful technopreneur in UAE. The mediation outcomes of digital enablers indicate a positive relationship between leadership factors and successful technopreneur in UAE.